Comparison of Effectiveness of Sublingual Versus Vaginal Misoprostol Use for Labour Induction at Term Pregnancy - Yadav, Poonam; Singh, Keerti; Nesar, Nazia; Verma, Shikha; Sharma, Sonali (Journal of Neonatal Surgery, 2025)
Background: Labour induction is a common obstetric intervention to facilitate vaginal delivery when prolonged pregnancy poses risks to maternal or fetal health. Misoprostol, a prostaglandin E1 analogue, is widely used for cervical ripening and labour induction, but the optimal route of administration remains debated. This study aimed to compare the efficacy and safety of sublingual versus vaginal misoprostol in term pregnancies. Methodology: A randomized prospective trial was conducted at IIMSR, Lucknow (2023–2025), involving 128 term pregnancies. Participants were randomly assigned to the sublingual (Group A, n=64) or vaginal (Group B, n=64) misoprostol group. Misoprostol (25 mcg) was administered every 4 hours, up to six doses, unless active labour occurred. Primary outcomes included vaginal delivery within 24 hours and induction-to-delivery interval, while secondary outcomes assessed cesarean rates, neonatal morbidity, and adverse drug effects. Statistical analysis was performed using SPSS 23.0, with a significance threshold of p<0.05. Results: In the present study, labour induction was more frequent after 37 weeks (68.75% vaginal vs. 57.81% sublingual). G1P0L0 was the most common parity in both groups. Higher misoprostol doses were required in the vaginal group. Cesarean rates were comparable (64.06% vaginal vs. 62.50% sublingual), and neonatal complications, mainly respiratory distress, were similar (53.13% vs. 51.56%). Maternal side effects were more frequent in the sublingual group (64.06% vs. 53.12%). Conclusion: We concluded that, both sublingual and vaginal misoprostol are effective for labour induction. The choice of route should be individualized based on patient preference, clinical conditions, and resource availability.